(untitled) (European Journal of Pure and Applied Mathematics, 2025)
We derive sine and cosine trigonometric functions by exploring the qualitative properties of differential equations. Further we demonstrated that the two functions are periodic. Additionally we derived the sine and cosine of sums and differences of two angles from differential equations. The oscillations of the solutions of second-order differential equations are examined along with related theorems and techniques.